(3TQM GdQSGdI GdCadGWhfjI aj Yde GdejRGfs - (3eLghds ((3eUdM GdOjf Hf SfGf s)
(3ChdgG (B:s
(3hHYO abO cGf ehdGfG GdC(B'(3Xe GdSdWGf CHh GdaJM NOGhfOcGQ eMeO NGf JZeOg Gddg HZaQGfg s
(3BNQgG (B:s
(3EPG cGfJ VYa GdQUGU cGf KdKkG GdUMf GdaVI hGdKdK GdQUGU ajchf GdaVd fUa YTQ GdKdKjf GdUMf GdaVI hGdKdK GdQUGU ajchf GdaVd fUa YTQ GdKdjf hYTQ GdKdK hPdc KdKG YTQ GdLedI s
(3JCdja HYV YdeGA GdQhe GdCJQGcs
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B4 - (3U (B67 s
Keywords: (3GdcjejGA h GdWHjYjGJs